Cox rings of du Val singularities - Laura Facchini; Victor González-Alonso; Michał Lasoń (Le Matematiche, 2011)
In this note we introduce Cox rings of singularities and explicitly compute them in the case of du Val singularities Dn , E6 , E7 and E8 .